Language Transformation In The Digital Era On Whatsapp: Issues And Solutions Of Using Emojis And Stickers As Replacements For Words Among Students - Siska Mustikawati Hasibuan; Ayudiah Cisita; Salabila Eka Ananda; Velissa Grace Aulia Situmorang; M. Natsir (PT. Intelek Cendikiawan Nusantara, 2024)
This article discusses the transformation of language in the digital era, particularly through the use of emojis and stickers as substitutes for words among university students using WhatsApp. The study identifies challenges arising from the use of these visual symbols, such as meaning ambiguity, misunderstandings, and a decline in verbal communication quality. Employing a qualitative research method and survey approach, data were collected through online questionnaires and conversation analysis in WhatsApp groups. The findings reveal that while emojis and stickers can enrich communication, excessive reliance on these symbols can hinder students' ability to communicate verbally and formally. This article also offers solutions to improve communication quality in academic settings and emphasizes the importance of developing verbal communication skills in the digital age.